Solve by factorising: From Quadratic Equation
![16. \: \frac{ 1}{a + b + x} = \frac{1}{a} + \frac{1}{b} + \frac{1}{x} 16. \: \frac{ 1}{a + b + x} = \frac{1}{a} + \frac{1}{b} + \frac{1}{x}](https://tex.z-dn.net/?f=16.+%5C%3A++%5Cfrac%7B+1%7D%7Ba+%2B+b+%2B+x%7D++%3D++%5Cfrac%7B1%7D%7Ba%7D++%2B++%5Cfrac%7B1%7D%7Bb%7D++%2B++%5Cfrac%7B1%7D%7Bx%7D+)
; a + b # 0 , x # 0
Ans: - a , - b
Standard:- 10
Content Quality Solution Required
❎Don't Spamming ❎
Answers
Answered by
7
Hey!!!
Good Evening
Difficulty Level : Super Extremely High(one of the most difficult questions)
Chances of being asked in Board : 90%
____________________
We have
![\frac{1}{a + b + x} = \frac{1}{a} + \frac{1}{b} + \frac{1}{x} \frac{1}{a + b + x} = \frac{1}{a} + \frac{1}{b} + \frac{1}{x}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Ba+%2B+b+%2B+x%7D++%3D++%5Cfrac%7B1%7D%7Ba%7D++%2B++%5Cfrac%7B1%7D%7Bb%7D++%2B++%5Cfrac%7B1%7D%7Bx%7D+)
Now understand well, take the 1/x to the LHS side and we will have the RHS only of a and b.
Let's solve
=> 1/(a + b + x) - 1/x = 1/a + 1/b
![= > \frac{x - (a + b + x)}{x(a + b + x)} = \frac{a + b}{ab} = > \frac{x - (a + b + x)}{x(a + b + x)} = \frac{a + b}{ab}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7Bx+-+%28a+%2B+b+%2B+x%29%7D%7Bx%28a+%2B+b+%2B+x%29%7D+%3D++%5Cfrac%7Ba+%2B+b%7D%7Bab%7D+)
![= > \frac{ - (a + b)}{x(a + b + x)} = \frac{(a + b)}{ab} = > \frac{ - (a + b)}{x(a + b + x)} = \frac{(a + b)}{ab}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B+-+%28a+%2B+b%29%7D%7Bx%28a+%2B+b+%2B+x%29%7D++%3D++%5Cfrac%7B%28a+%2B+b%29%7D%7Bab%7D+)
Cancelling (a + b) and then cross Multiplying
=> - ab = x(a + b + x)
=> -ab = ax + bx + x²
=> x² + ax + bx + ab = 0
=> x(x + a) + b(a + x) = 0
=> (x + a)(x + b) = 0
=> x = - a or => x = - b <<<< Answer
______________
Hope this helps ✌️
Good Morning
Good Evening
Difficulty Level : Super Extremely High(one of the most difficult questions)
Chances of being asked in Board : 90%
____________________
We have
Now understand well, take the 1/x to the LHS side and we will have the RHS only of a and b.
Let's solve
=> 1/(a + b + x) - 1/x = 1/a + 1/b
Cancelling (a + b) and then cross Multiplying
=> - ab = x(a + b + x)
=> -ab = ax + bx + x²
=> x² + ax + bx + ab = 0
=> x(x + a) + b(a + x) = 0
=> (x + a)(x + b) = 0
=> x = - a or => x = - b <<<< Answer
______________
Hope this helps ✌️
Good Morning
VijayaLaxmiMehra1:
In easy way solution :))
Similar questions